Time to antenatal care booking and its predictors among pregnant women in East Africa: a Weibull gamma shared frailty model using a recent demographic and health survey - Abel Endawkie; Shimels Derso Kebede; Kaleab Mesfin Abera; Eyob Tilahun Abeje; Ermias Bekele Enyew; Chala Daba; Lakew Asmare; Fekade Demeke Bayou; Mastewal Arefaynie; Anissa Mohammed; Abiyu Abadi Tareke; Awoke Keleb; et al. (Frontiers Media S.A., 2024)
BackgroundAntenatal care (ANC) is an important component of maternal and child healthcare. The World Health Organization (WHO) recommends that pregnant women book their ANC contact at or before 12 weeks of gestational age. However, in East Africa, evidence on whether the WHO recommendations have been followed is limited. Therefore, this study aimed to determine the time to ANC booking and its predictors among pregnant women in East Africa.MethodThis study was conducted among 86,662 pregnant women in East Africa. The time to ANC booking was estimated using the Kaplan-Meier (K-M) survival estimate. A Weibull gamma shared frailty model was used to determine the predictors of time to the first ANC visit. An adjusted hazard ratio (AHR) with a 95% confidence interval (CI) was reported.ResultThe median time to ANC booking among pregnant women in East Africa was 4 ± 2 months. Maternal education at the primary (AHR = 1.01, 95% CI: 1.02-1.25), secondary (AHR = 1.03, 95% CI: 1.02-1.05), and higher level (AHR = 1.40, 95% CI: 1.30-1.50); husband's education level at the primary (AHR = 1.08, 95% CI: 1.06-1.09), secondary (AHR = 1.12, 95% CI: 1.10-1.13), and higher (AHR = 1.08, 95% CI: 1.07-1.10) levels as compared to with no education; a middle-class wealth status (AHR = 1.66, 95% CI: 1.60-1.70), being rich (AHR: 1.60, 95% CI: 1.56-1.73), high community-level maternal literacy (AHR = 1.05, 95% CI: 1.04-1.06), high community-level poverty (AHR = 0.99, 95% CI: 0.98-0.99), previous Cesarean section (CS) (AHR = 1.35, 95% CI: 1.33-1.39), and unwanted pregnancy (AHR = 0.74, 95% CI: 0.72-0.77) were predictors of the time to ANC booking.ConclusionThe median time to ANC booking among pregnant women in East Africa is longer than the new WHO recommendation. Maternal and husband education, high community-level maternal literacy, a better household, community-level wealth index, and previous CS increase the likelihood of an early ANC booking. However, unwanted pregnancy lowers the likelihood of an early ANC booking. Therefore, strengthening systematic efforts to improve women's and their husbands' educational status, encouraging women's education in the community, providing economic support for women with low wealth status and poor communities, encouraging wanted pregnancy, and providing accessible counseling services for women with unwanted pregnancies will help to encourage early ANC booking among pregnant women in East Africa.